The distance-quality trade-off in women’s choice of family planning provider in North Eastern Tanzania - Iqbal Shah; Bilikisu Elewonibi; Ryoko Sato; Rachel Manongi; Sia Msuya; David Canning (BMJ Global Health)
Introduction Studies on the determinants of contraceptive use often consider distance to the nearest health facility offering contraception as a key explanatory variable. Women, however, may not seek contraception from the nearest facility, rather opting for a more distant facility with better quality services or to ensure greater privacy and anonymity.Methods The dataset used include the name of facility where each women obtained contraception, measures of facility quality, and the distance between each woman’s home and 39 potential facilities she might visit. We use a conditional-multinomial logit model to estimate the determinants of her facility choice to visit and how women tradeoff travelling longer distances to use higher quality facilities.Results Only 33% of woman who received contraception from a health facility used their nearest facility. While the nearest facility was 1.2 km away, the average distance to facility used was 2.9 km, indicating women are willing to travel significantly longer distances for higher quality. Women prefer facilities that specialise in providing contraception, provide a large range of methods, do not suffer from stock outs and do not charge fees. Furthermore, on average, women are willing to travel an additional 2 km for a facility that offers more family planning methods, 4.7 km for a facility without one additional health service, 9 km for a facility without fees for contraception and 11 km for a facility not experiencing stock out of an additional contraception.Conclusion Our results suggest that quality of services provided is an important driver of facility choice in addition to distance to facility.